Intrinsic membrane glycoproteins with cytosol-oriented sugars in the endoplasmic reticulum. - Abeijon, C (1988)
We have examined the topography of N-acetylglucosamine-terminating glycoproteins in membranes from rat liver smooth and rough endoplasmic reticulum (SER and RER). It was found that some of these glycoproteins are intrinsic membrane proteins with their sugars facing the cytosolic rather than the luminal side. This conclusion was reached by using vesicles from the SER and RER that were sealed and of the same topographical orientation as in vivo. These vesicles were incubated with UDP-[14C]galactose (which does not enter the vesicles) and saturating amounts of soluble galactosyltransferase from milk, an enzyme that does not penetrate the lumen of the vesicles and that specifically adds galactose to terminal N-acetylglucosamine in a beta 1-4 linkage. Radioactive galactose was mainly transferred to SER proteins of apparent molecular mass 56 and 110 kDa and to a lesser extent to RER and SER proteins of apparent molecular mass 46 and 72 kDa. These proteins are intrinsic membrane proteins, based on the inability of sodium carbonate at pH 11.5 to remove them from the membranes. Studies with peptide N-glycosidase F and chemical beta-elimination showed that the 56-kDa protein of the SER vesicles contained terminal N-acetylglucosamine in an O-linkage to the protein. The above results suggest that some sugars of glycoproteins in the endoplasmic reticulum may attain their final orientation in the membrane by mechanisms yet to be determined.